Asosiasi Jenis-jenis Pohon Dominan di Cagar Alam Gunung Tilu - Adi Susilo (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Association is a relationship between living things in an environment. Between two plants species, for example, there can be a linkage. Positive associations occur when a plant species occur along with other specific plant species while negative associations occur in the opposite condition. The purpose of this research was to identify the association among the dominant tree species in the Mount Tilu Nature Reserve by making a permanent plot of 100 m x 100 m divided into 25 subplots of  20 m x 20 m to inventory the trees. On each subplot, a smaller size 5 m x 5 m and 1 m x 1 m plots were nested to inventory successively saplings and seedlings. The dominant tree species were determined by vegetation analysis. The association indexes were calculated by a contingency table of 2 x 2 accompanied by association coefficient. The Result showed that the vegetation composition on the tree level consists of 8 families, 11 genera 16 species, on sapling level consist of  9 families, 10 genera, 12 species and on the seedling level consist of 9 families, 9 genera, and 12 species. The dominant species on tree level were Litsea accedentoides, Lithocarpus sundaicus, Litsea javanica and Liquidambar excelsa, on the sapling level were Schima wallichii, Liquidambar excelsa, Eupatorium triplinerve and Schefflera aromatica, on the seedling level were Schima wallichii, Ficus padana, Antidesma montanum and Nikolai speciosa.  The association analysis showed that Litsea javanica and Lithocarpus sundaicus were significantly associated negatively in contrary Litsea accedentoides and Lithocarpus sundaicus significantly associated positively